Social Representations Of Dreams - Sociological Study - Chouchane, Zohra (جامعة الوادي - University of Eloued, 2023)
يولد التساؤل السوسيولوجي عند الباحث من خلال التوتر الملاحظ بين حدث ما والسير الطبيعي العادي للمجتمع، فكثيرة هي الأفكار المحيّرة والمستقطبة للاهتمام في الحقل السوسيولوجي والتي تتطلب مهارة الباحث. وتتجلى هذه المهارة في قدرة الباحث على الانتقال من الاجتماع الخام أو من الحس المعطى الواقعي إلى إبستمولوجية الشيء المعطى. وأردنا من خلال ذا المقال الاجابة على السؤال التالي: هل تمثلات الأحلام تتأثر بالمتغيرات الاجتماعية مثل: الجنس، الانتماء الاجتماعي، الوسط الاجتماعي ... ترتبط تمثلات الأفراد بالمجتمع، حيث يتبنى الأفراد نظام التمثلات السائدة في المجتمع، وفي إطاره يفكرون ويشعرون. وتختلف هذه التمثلات باختلاف المجتمعات التي ولدوا فيها الأفراد، لذلك فإن كل نمط عقلي هو رمزي مرتبط بنوع المجتمع. من هنا تختلف التمثلات باختلاف المجتمعات وبنيتها التاريخية والاجتماعية، وهذه التمثلات الاجتماعية تهيمن على عقيدة الأفراد. وتتحكم في الأفراد لأنها مؤسسة اجتماعيا ومشتركة بين الأفراد، ولها هدف يتمثل في بناء واقع مشترك لمجموعة اجتماعية ما، بحيث ترتبط تلك المجموعة بنفس التمثلات. تعبر التمثلات عن الانتماء الاجتماعي للأفراد من خلال دمجهم للممارسات والخبرات والنماذج السلوكية والمعرفية المشركة بين أفراد. بمعنى آخر هي شكل من أشكال المعرفة يختلف عن المعرفة العلمية، فهو آلي وساذج، وينشأ بطريقة عفوية ويظهر بسبب إثارة بسيطة أو وجود رمز بسيط تلقائي وليس عن قصد. بناءً على ما سبق، ولتأكيد ذلك قمنا بتحليل عينة قصدية من 100 فرد وركزنا على العناصر التالية: إيمان الأفراد بالأحلام حسب الجنس. إيمان الأفراد بالأحلام حسب السن. إيمان الأفراد بالأحلام حسب الوسط الاجتماعي. وبناءً على ما سبق، نستنتج أن المتغيرات الاجتماعية تؤثر على تمثلات الأفراد وتجعلهم يؤمنون بمحتوى الأحلام. وهذه المتغيرات هي الجنس، السن والوسط الاجتماعي. Abstract: The sociological question arises in the researcher through the perceived tension between an event and the normal course of society. Many are bewildering and polarizing ideas of interest in the sociological field that require the researcher's skill. The researcher’s skill and ingenuity is evident from his ability to move from the raw social or from the factual given sense to the epistemology of the given thing by employing the researcher to a compatible analysis model and the sociological research specificity . This is what prompts us to ask the following question : Are dream representations affected by social variables such as: gender, social affiliation, social milieu ... The representations of individuals are linked to society, as individuals are surprised by the system of the dominant representations of society , Within its framework, you think and explain well their feelings, and these representations differ according to the society in which they were born, wherever they are, so each mental pattern is symbolic and related to the type of society, where its institutions and applications are . From this, representations differ according to different societies and their historical and social structure, which is social representations that dominate the belief of individuals. It controls individuals because it is socially constructed and shared between them, and it has a point and an application goal and aims to build a common reality for a social group, so that that group is linked by the same representations . Representations express the social belonging of individuals through their incorporation of practices, experiences, and behavioral and cognitive models. In other words, it is a form of knowledge that differs from scientific knowledge, as it is automatic and naive, and it arises in a spontaneous way and appears because of an exciting or symbol and spontaneously and not intentionally . Based on the above, we analyzed an intended sample of 100 individuals and focused on the following themes : ✓ Individuals’ belief in dreams according to gender . ✓ Individuals’ belief in dreams according to age . ✓ Individuals believe in dreams according to the social milieu . Based on the above, we conclude that social variables affect individuals’ representations and make them believe in dreams. These variables are gender, age, and social milieu.
مقال
Keywords: dreams, representations, belief, gender, social affiliation, social milieu